2015
DOI: 10.1002/bit.25563
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of whole‐cell mitochondrial motility and its dependence on cytoarchitectural integrity

Abstract: Current methodologies used for mitochondrial motility analysis tend to either overlook individual mitochondrial tracks or analyze only peripheral mitochondria instead of mitochondria in all regions of the cell. Furthermore, motility analysis of an individual mitochondrion is usually quantified by establishing an arbitrary threshold for “directed” motion. In this work, we created a custom, publicly available computational algorithm based on a previously published approach (Giedt et al., 2012) in order to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 33 publications
(55 reference statements)
1
65
1
Order By: Relevance
“…Consistent with the ‘tip-tracking’ model described above, a number of research studies showed that mitochondrial motility was impaired upon microtubule depolymerization (Kandel et al, 2015; Ligon and Steward, 2000; Morris and Hollenbeck, 1995; Muller et al, 2005; Yi et al, 2004). While a consensus has emerged regarding the role of the microtubular cytoskeleton, conflicting results have been published on the relationships between the actin cytoskeleton and mitochondrial movements.…”
Section: Descriptions Of Mitochondrial Morphologysupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with the ‘tip-tracking’ model described above, a number of research studies showed that mitochondrial motility was impaired upon microtubule depolymerization (Kandel et al, 2015; Ligon and Steward, 2000; Morris and Hollenbeck, 1995; Muller et al, 2005; Yi et al, 2004). While a consensus has emerged regarding the role of the microtubular cytoskeleton, conflicting results have been published on the relationships between the actin cytoskeleton and mitochondrial movements.…”
Section: Descriptions Of Mitochondrial Morphologysupporting
confidence: 58%
“…While a consensus has emerged regarding the role of the microtubular cytoskeleton, conflicting results have been published on the relationships between the actin cytoskeleton and mitochondrial movements. Actin filament depolarization was shown to influence mitochondrial motility either negatively (Muller et al, 2005; Quintero et al, 2006) or positively (Ligon and Steward, 2000; Morris and Hollenbeck, 1995), partly depending on the cell type analyzed (Kandel et al, 2015). Interestingly, depolymerizing the actin cytoskeleton was recently suggested to blunt mitochondrial motility only in neuronal processes, and not in the cell body (Narayanareddy et al, 2014), providing further support to the idea that distinct control mechanisms may operate in different spatially-restricted cytoplasmic regions.…”
Section: Descriptions Of Mitochondrial Morphologymentioning
confidence: 99%
“…Adult human dermal fibroblasts between passages 1 and 5 (Lifeline Cell Technology, Walkersville, MD) were cultured in FibroLife cell culture media (Lifeline Cell Technology) as previously described [16]. Cells were seeded approximately 48 hours prior to experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in mitochondrial inner membrane potential and morphology in single cells were assessed using wide-field fluorescence microscopy as previously described [16]. Cell viability was also measured using this setup.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation